Spatial Structure of Industries in Selected Governorates - Abd Aladheem Shukur, Ammar (Al-Adab Journal, 2019)
It is known that the industrial structure of any province, especially in the provinces that have advanced industrial potential is called the economic base and therefore the analysis of the industrial or economic structure of any province aims to know the economic construction of the region in terms of knowledge and job performance on the other hand. Therefore, researchers focus on determining the nature of industrial economic resources in the region (minerals, energy, labor) and then determine the general pattern of distribution of existing industry in the region or can be, and know the factors that led to that type of spatial distribution of industrial activities and on the basis of identification The tracks and trends of the industrial structure in the region shall be the decision on industrial settlement (specialization or diversity in quantity and quantity) and according to the nature and costs of exploitation In order to draw an integrated picture of the characteristics of the industrial spatial structure of the provinces in Iraq, the research used a quantitative method based on indicators of the industrial sector in five provinces, and found that the results of the research have created specific industries that must be specialized and future direction to attention to them according to the quantitative method Which adopted (the method of transformation and contribution (quota)) to achieve spatial development in all governorates and between the areas of the province itself, especially those suffering from developmental imbalance.